Synthesis, Antibacterial Activity and In Silico Study of 1-(2-ethyl acetate)-2-styryl 5-nitroimidazole Derivatives - Aragaw, Misgana; Degu, Sileshi; Abebe, Abiy; Abebayehu, Mekonnen; Bedane, Kibrom Gebreheiwot; Bisrat, Daniel; Tadesse, Solomon (Anti-Infective Agents, 2025)
BackgroundFor more than six decades, the use of metronidazole has been limited to anaerobic microorganisms. However, there are accounts of metronidazole derivatives exhibiting strong effectiveness against facultative anaerobic bacteria, suggesting that there may be another mechanism of action for metronidazole. Recent studies have shown that the enzyme FabH (β-ketoacyl-acyl carrier protein synthase III), responsible for the first step of fatty acid biosynthesis (FAB), is a promising target for nitroimidazole derivatives that can be used as an effective anti-infective agent.ObjectiveThis study aimed to synthesize 1-(2-ethyl acetate)-2-styryl nitroimidazole derivatives and evaluate their in vitro and in silico antibacterial activity.MethodsWe synthesized 2-styryl 5-nitroimidazole derivatives by first condensing metronidazole with benzaldehydes and then carrying out an acetylation reaction. We evaluated the antimicrobial activity of the synthesized compounds against three Gram-positive bacterial strains (Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus agalactiae) and three Gram-negative bacterial strains (Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae) using a two-fold serial dilution MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay.ResultsCompounds 2 and 4 exhibited the highest level of antibacterial effectiveness, with minimum inhibitory concentrations (MIC) of 1.56 μg/mL against S. agalactiae and 3.13 μg/mL against P. aeruginosa. Compounds 2 and 4 also exhibited potent activity against K. pneumonia, with an MIC value of 6.25 μg/mL and 12.5 μg/mL, respectively. Molecular docking studies revealed that both compounds have favorable hydrophobic and electrostatic interactions with conserved residues in the binding site of the E. coli β-Ketoacyl-acyl carrier protein synthase III (FabH) complex.ConclusionAcetylation of 2-styryl-5-nitroimidazoles improved both their biological activity and binding interaction with the target protein.
Keywords: β-ketoacyl-acyl carrier protein synthase III